PARTICULAR ASPECTS OF ORTHODONTIC DEBONDING TECHNIQUES DURING CERAMIC BRACKETS REMOVAL - Nikolaos Karvelas; Alice Chehab; Raluca Maria Vieriu; Bogdan Radu Dragomir; Carmen Savin; Irina Zetu (Romanian Dental Association for Education, 2021)
Enamel cracks or enamel microcracks are defined as a fracture at the enamel surface usually when the ceramic brackets debonding procedure takes place. Enamel loss is a common problem during orthodontic debonding, in which enamel is damaged and irreversible morphological characteristics arise, which are quite visible by the naked eye. Particularly the removal of ceramic brackets generates several complications as tooth staining, plaque accumulation, carious lesions, and hypersensitivity. Ceramic brackets can be damaged the enamel surface although, debonding techniques seem to decrease the enamel cracks providing an efficient and reliable method.